Correction of bone defects by tissue Engineering - Saucedo Acuña, Rosa Alicia; Galicia García, Mónica; Ríos Arana, Judith Virginia; Reyes López, Simón Yobanny (Acta Universitaria, 2012)
Currently, bone defects cases represent a major impact on health due to how often they occur because of trauma, fractures, congenital or degenerative diseases. Now, bone implants to large volume are severely restricted because of the diffusion limitations in the interaction with the environment of the host for nutrients, gas exchange and waste disposal. That is why the correction of bone defects has become very important in the field of tissue engineering looking to improve clinical strategies for treatment. The purpose of this review is to provide an overview of the development of scaffolds for bone tissue regeneration, showing the progress made in the in vitro and in vivo in recent decades
Keywords: Array; Array; Array